Ag-graphene/PEG composite phase change materials for enhancing solar-thermal energy conversion and storage capacity. (1st March 2019) - Zhang, Yuang; Wang, Jiasheng; Qiu, Jinjing; Jin, Xin; Umair, Malik Muhammad; Lu, Rongwen; Zhang, Shufen; Tang, Bingtao
Graphical abstracts: Enhanced light absorption capacity, reduced thermal radiation and high solar-to-thermal energy storage efficiency can be achieved by using of Ag–GNS/PEG composites. Highlights: A new strategy to improve photothermal conversion efficiency of PCMs was developed. The composites can harvest and convert visible light efficiently (η = 88.7–92.0%). The composites exhibit high phase change enthalpies (166.1–177.2 J/g). The composites show enhanced thermal conductivities and shape-stabilities. Abstract: In view of the excellent characteristic of thermal energy storage, phase change materials (PCMs) are of great significance for improving the efficiency of solar thermal energy utilization. However, the direct thermal effect of visible-light (40% of solar radiation) is very low. In order to improve the capabilities of visible-light absorption and photothermal conversion, we reported novel and efficient sunlight-driven PCMs based on polyethylene glycol (PEG) supported by Ag nanoparticle-functionalized graphene nanosheets (Ag–GNS). The multi-folded layered structure provides Ag–GNS a large surface area to support PEG for achieving the shape stability before and after phase transition. Meanwhile, based on the local surface plasma resonance effect of Ag, Ag has high visible light selective absorption and infrared reflectance, which can give Ag–GNS enhanced light absorption capacity and reduced thermal radiation. So Ag–GNS/PEG can harvest sunlight and convert light to thermal energy with significantly higher efficiency ( η = 88.7–92.0%). Moreover, Ag–GNS/PEG composites exhibit enhanced thermal conductivities (49.5–95.3%), high energy storage densities (>166.1 J/g), high thermal energy storage/release rates and outstanding form-stable properties. Therefore, this novel sunlight-driven composite can be potentially used for clean and efficient utilization of solar energy.